Plasminogen activator inhibitor-1 4G/5G polymorphism is associated with metabolic syndrome parameters in Malaysian subjects - Al-Hamodi, Z.H.; Saif-Ali, R.; Ismail, I.S.; Ahmed, K.A.; Muniandy, S. (2012)
The plasminogen activator inhibitor-1 4G/5G and tissue plasminogen activator Alu-repeat insertion/deletion polymorphisms might be genetic determinations of increased or decreased of their plasma activities. The aim of this study was to investigate the association of plasminogen activator inhibitor-1 4G/5G and tissue plasminogen activator Alu-repeat I/D polymorphisms with metabolic syndrome parameters in normal Malaysian subjects and to assess the impact of these polymorphisms on their plasma activities and antigens. The genetic polymorphisms were genotyped in 130 normal subjects. In addition, the plasma activities and antigens of plasminogen activator inhibitor-1 and tissue plasminogen activator as well as levels of insulin, glucose, and lipid profile at fasting state were investigated. The subjects with homozygous 4G/4G showed association with an increased triglyceride (p = 0.007), body mass index (p = 0.01) and diastolic blood pressure (p = 0.03). In addition, the plasminogen activator inhibitor-1 4G/5G polymorphism modulates plasma plasminogen activator inhibitor-1 activity and antigen and tissue plasminogen activator activity (p = 0.002, 0.014, 0.003) respectively. These results showed that, the plasminogen activator inhibitor-1 4G/5G polymorphism is associated with metabolic syndrome parameters, plasminogen activator inhibitor-1 and tissue plasminogen activator activities in Malaysian subjects, and may serve to increase the risk of type 2 diabetes and cardiovascular disease in Malaysian subjects.